2002
DOI: 10.1051/0004-6361:20011543
|View full text |Cite
|
Sign up to set email alerts
|

X–ray and optical monitoring of the peculiar source 4U 1700+24/V934 Her

Abstract: Abstract. We report on ASCA and BeppoSAX X-ray broad band observations of the galactic low-luminosity X-ray source 4U 1700+24 performed on 1995 and 1998, respectively, and on (quasi-)simultaneous ground observations of its optical counterpart, V934 Her, from the Loiano 1.5-meter telescope. In order to better understand the nature of the source we also analyze public archival ROSAT and RXTE data as well as the RXTE ASM light curve of 4U 1700+24; we also re-analyze a 1985 EXOSAT pointing. The optical spectra are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
85
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 62 publications
16
85
1
Order By: Relevance
“…The latter characteristic is due to the low X-ray luminosity when compared to the bolometric luminosity of a M4 III star (∼2 ×10 36 erg s −1 ; Lang 1992); so, reprocessing of variable X-ray emission is completely lost into the glare of the M-type giant companion. Thus, a scenario similar to that described by Masetti et al (2002) for 4U 1700+24 may also be applicable to the system 4U 1954+319.…”
Section: U 1954+319mentioning
confidence: 95%
See 3 more Smart Citations
“…The latter characteristic is due to the low X-ray luminosity when compared to the bolometric luminosity of a M4 III star (∼2 ×10 36 erg s −1 ; Lang 1992); so, reprocessing of variable X-ray emission is completely lost into the glare of the M-type giant companion. Thus, a scenario similar to that described by Masetti et al (2002) for 4U 1700+24 may also be applicable to the system 4U 1954+319.…”
Section: U 1954+319mentioning
confidence: 95%
“…Garcia et al (1983), using the X-ray position afforded by the HEAO-1 satellite, identified this source in the optical with a "normal" M-type giant star, HD 154791, located at ∼800 pc from Earth. Masetti et al (2002) gave a more accurate spectral classification (M2−3 III) to this putative optical companion and, in turn, a new distance estimate (d = 420 pc). The latter authors moreover explained the absence of the features typical of accreting systems in the optical spectrum of HD 154791 as due to the fact that the luminosity of the giant star is ∼200 times larger that any possible optical emission from the accreting stream, and so the latter is overwhelmed by the former.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Among the large X-ray binary zoo, we know so far only another system hosting a neutron star (NS) with a red giant companion: 4U 1700+24 ( [16,9]). GX 1+4 shows an unpredictably variable X-ray flux on timescales from hours to decades.…”
Section: Introductionmentioning
confidence: 99%